Event recognition and anomaly detection using machine learning - Peng, Xinggan (Nanyang Technological University, 2024)
Abnormal event recognition and anomaly detection aim to discover incidents, patterns or objects that do not conform to expected behaviour. In this thesis, our focus includes two parts: “illegal parking” activity detection tasks from images and anomaly detection with applications to time series data.